Current Research and Emerging Directions in Emotion-Cognition Interactions - Mara Mather (Frontiers Research Topics, 2015)
Emotion can impact various aspects of our cognition and behavior, by enhancing or impairing them (e.g., enhanced attention to and memory for emotional events, or increased distraction produced by goal-irrelevant emotional information). On the other hand, emotion processing is also susceptible to cognitive influences, typically exerted in the form of cognitive control of motion, or emotion regulation. Despite important recent progress in understanding emotion- cognition interactions, a number of aspects remain unclear. The present book comprises a collection of manuscripts discussing emerging evidence regarding the mechanisms underlying emotion- cognition interactions in healthy functioning and alterations associated with clinical conditions, in which such interactions are dysfunctional. Initiated with a more restricted focus, targeting (1) identification and in depth analysis of the circumstances in which emotion enhances or impairs cognition and (2)identification of the role of individual differences in these effects, our book has emerged into a comprehensive collection of outstanding contributions investigating emotion-cognition interactions, based on approaches spanning from behavioral and lesion to pharmacological and brain imaging, and including empirical, theoretical, and review papers alike. Co-hosted by the Frontiers in Neuroscience - Integrative Neuroscience and Frontiers in Psychology - Emotion Science, the contributions comprising our book and the associated research topic are grouped around the following seven main themes, distributed across the two hosting journals: I. Emotion and Selectivity in Attention and Memory; II. The Impact of Emotional Distraction; Linking Enhancing and Impairing Effects of Emotion; III. What Really is the Role of the Amygdala?; IV. Age Differences in Emotion Processing; The Role of Emotional Valence; V. Affective Face Processing, Social Cognition, and Personality Neuroscience; VI. Stress, Mood, Emotion, and the Prefrontal Cortex; The Role of Control in the Stress Response; VII. Emotion-Cognition Interactions in Clinical Conditions. As illustrated by the present collection of contributions, emotion-cognition interactions can be identified at different levels of processing, from perception and attention to long- term memory, decision making processes, and social cognition and behavior. Notably, these effects are subject to individual differences that may affect the way we perceive, experience, and remember emotional experiences, or cope with emotionally challenging situations. Moreover, these opposing effects tend to co-occur in affective disorders, such as depression and PTSD, where uncontrolled recollection of and rumination on distressing memories also lead to impaired cognition due to emotional distraction. Understanding the nature and neural mechanisms of these effects is critical, as their exacerbation and co-occurrence in clinical conditions lead to devastating effects and debilitation. Hence, bringing together such diverse contributions has allowed not only an integrative understanding of the current extant evidence but also identification of emerging directions and concrete venues for future investigations.